TUKAR MENUKAR HAK ATAS TANAH ANTAR WILAYAH OLEH PEJABAT PEMBUAT AKTA TANAH - Wiranegara, I Made Adi; Wairocana, I Gusti Ngurah; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan, 2017)
Land is one of the most important part of human survival. In addition to the land as a residence, land as well as a place to seek fortune, and therefore every human being needs to control a piece of land for the purposes of life . Increasing the need for land for business activities, the increasing need for support in the form of legal certainty in the field of land to reduce the occurrence of conflict in the community . Therefore, in ensuring law and order in society, the State is very concerned to regulate both about control and about the transition or transfer of land rights in Indonesia. One of the transfer of land right arrangements known in the land laws in Indonesia is the "Land Swap". Substantively, exchange or swap is part of the engagement that was born out of the agreement, therefore, it is subject to the principle of freedom of contract, but because the object is a land right, the implementation must comply with the formal requirements set out in the legislation in the field of agrarian or land law. To exchange land of which location of land between the land located in Badung with land located in Denpasar according to the Indonesian Government Regulation Number 24 of 2016 about the amendment to Government Regulation Number 37 of 1998 on regulations on the Positions of Land Deed Officials, the local authority pursuant to article 12 of PPAT work area is in one province. Therefore for the exchange of land as aforesaid, the Deed of PPAT is enough in one land certificate. The research method using juridical empirical method namely by using field data (field research) as the primary data and legislation as well as books that discuss the problems as the secondary data. Based on the data collected and analyzed qualitatively, it can be concluded that the exchange of land that located between Badung and land Denpasar City could not be implemented because the Indonesian Government Regulation Number 24 of 2016 about the amendment to Regulation of Government Number 37 of 1998 regarding regulation of Land Deed Officials Position has not adhered to because of factor of lack of coordination between the relevant parties, and the legal cultural factors of the human resources who implementing the regulations.